Maria Lacerda de Moura e o estudo científico da criança patrícia em Minas Gerais (1908-1925) - Paula Cristina David Guimarães (2016)
This work investigates the project of child scientific study conceived by Maria Lacerda de Moura between the years 1908 and 1925. This interval is established taking into consideration the beginning of her career as a teacher of the Normal School of Barbacena, MG (1908) and her last publication directed to the education of children (1925). For the research, several historical sources were listed, such as the application sent by Maria Lacerda de Moura to the Secretary of the Interior of Minas Gerais, requesting authorization to conduct experimental psychology experiences with children from Barbacena schools; the opinions issued by that body on the request of the teacher; part of the intellectual production of Maria Lacerda de Moura, which includes books, papers and conferences; documents from the Normal School where she worked, such as inspection books and minutes of the congregation; as well as newspapers about educational legislation published in that period. With the data collected, the interest was: 1) to know the formation of Maria Lacerda de Moura, checking to what extent she contributed with her ideas about science applied to education of children; 2) to describe and analyze the application of the teacher along with the views expressed, identifying how was the reception of the experiences of experimental psychology in the state of Minas Gerais at the time; 3) to locate the intellectual context in which Maria Lacerda de Moura thought her project of scientific study of childhood; 4) to identify the experiences she sought to develop in Barbacena, as well as the authors and studies that guided her work. For data analysis, the understanding of the power relations and the production of knowledge and truth was important to understand a project that has generated a series of discourses on the insertion of scientific knowledge in Minas Gerais schools. The results indicate that the formation of Maria Lacerda de Moura directly influenced her project of child scientific study. They also point out that the reception of her project in Minas Gerais was pervaded by suspicion concerning, sometimes, the nascent experimental psychology, and, other times, the womanly condition of her creator. They indicate, moreover, that the possibility of writing of this project took place amid various dialogues with different sciences, such as medicine, physiology, soil science and psychology.